1997
DOI: 10.1046/j.1537-2995.1997.37197176946.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cytokine accumulation and bacterial growth during storage of platelet concentrates at 4° C with retention of in vitro functional activity

Abstract: The storage of PCs at refrigerated temperatures inhibits the accumulation of white cell-produced cytokines in the PCs, an effect that could alleviate cytokine-associated febrile transfusion reactions The 4 degrees C storage was also bacteriostatic, which indicates that the storage of PCs at that temperature increases safety by decreasing the potential for sepsis. Thus, the ability to store PCs at 4 degrees C may allow extension of the storage limit beyond 5 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 29 publications
1
41
0
Order By: Relevance
“…Previous studies have also shown that metabolic suppression can result in preservation of PLT function, 50 which may also provide an explanation for the maintenance of aggregation in cold-stored PLTs. In addition, refrigerated storage reduces bacterial growth, 51,52 which is one of the primary reasons that the shelf life of PLTs is so limited.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also shown that metabolic suppression can result in preservation of PLT function, 50 which may also provide an explanation for the maintenance of aggregation in cold-stored PLTs. In addition, refrigerated storage reduces bacterial growth, 51,52 which is one of the primary reasons that the shelf life of PLTs is so limited.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] Unfortunately, the coldinflicted changes in GPIbα collectively defined as GPIbα clustering prevents rapid introduction into transfusion medicine. The present results describe the molecular mechanism of cold-induced GPIbα clustering.…”
Section: Discussionmentioning
confidence: 99%
“…Refrigerated storage of platelet products would be predicted to dramatically reduce the risk of bacterial growth [6, 7], permitting extended storage of platelets and bolstering product inventories. Competing technologies now under development might ultimately undermine these potential benefits [8].…”
mentioning
confidence: 99%